EFFECT OF INTRAVITREAL BEVACIZUMAB IN COMBINATION WITH POSTERIOR SUB-TENON TRIAMCINOLONE ON DIFFERENT LEVELS OF DIABETIC MACULAR EDEMA - Shafqat, Rubab; Habib, Muhammad Kashif; Najeeb, Sara; Sadiq, Muhammad Usman; Bashir, Aziz Jan; Sadiq, Muhammad Irfan (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the efficacy of Intravitreal Bevacizumab in combination with Posterior Subtenon Triamcinolone for treatment of different levels of diabetic macular edema.Study Design: Comparative cross sectional study.Place and Duration of Study: This study was done in Retina Clinic, Al Shifa Trust Eye Hospital, Rawalpindi, from Jul 2017 to Dec 2017. Methodology: Total of fifty-two patients were included in the study which were divided into two groups on the basis of foveal thickness (group 1 = Foveal Thickness 500μm). Results: Both groups were treated with combination of Intra-vitreal Avastin and Posterior Subtenon Triamcinolone. The percentage decrease in foveal thickness after 6 weeks of injection in group 1 was 30.08 ± 13.035% as compared to 38.88 ± 8.883% in group 2 (p=0.006). While the improvement in BCVA in both groups after 6 weeks of injection was same (0.2 ± 0.2 in Log MAR) (p=0.521).Conclusion: It is concluded that the use of Intravitreal Bevacizumab in combination with posterior subtenon triamcinolone for treatment of macular edema is more effective in foveal thickness >500μm as compared to thickness